Estimating Intergenerational Health Transmission in Taiwan with Administrative Health Records - Harrison Chang; Timothy J. Halliday; Ming-Jen Lin; Bhashkar Mazumder (Institute of Labor Economics (IZA), 2023)
We use population-wide administrative health records from Taiwan to estimate intergenerational persistence in health, providing the first estimates for a middle income country. We measure latent health by applying principal components analysis to a set of indicators for 13 broad ICD categories and quintiles of visits to a general practitioner. We find that the rank-rank slope in health between adult children and their parents is 0.22 which is broadly in line with results from other countries. Maternal transmission is stronger than paternal transmission and sons have higher persistence than daughters. Persistence is also higher at the upper tail of the parent health distribution. Persistence is lower when using inpatient data or when using total medical expenses and may overstate mobility. Health transmission is almost entirely unrelated to household income levels in Taiwan. We also find that that there are small geographic differences in health persistence across townships and that these are modestly correlated with area level income and doctor availability. Finally, by looking at persistence within health conditions that vary in their genetic component, we find little evidence that health persistence is driven by genetic factors.
Keywords: I1; J1; 330; intergenerational mobility; health; administrative data; genetics